Publications Received (Academy of Management Review, 2004)
A list is presented of books received by the publication for future review including “Creating a Strategic Human Resources Organization: An Assessment of Trends and New Directions,” by Edward E. Lawler III and Susan Albers Mohrman, “Benefit-Cost Analysis: Financial and Economic Appraisal Using Spreadsheets,” by Harry Campbell and Richard Brown, and “The Appreciative Inquiry Summit: A Practitioner's Guide for Leading Large-Group Change,” by James D. Ludema, Diana Whitney, Bernard J. Mohr, and Thomas J. Griffin.